Distribution and abundance of sacred monkeys in igboland, Southern Nigeria (2009)
Although primates are hunted on a global scale, some species are protected against harassment and killing by taboos or religious doctrines. Sites where the killing of sacred monkeys or the destruction of sacred groves is forbidden may be integral to the conservation of certain species. In 2004, as part of a distribution survey of Sclater’s guenon (Cercopithecus sclateri) in southern Nigeria, we investigated reports f sacred monkeys in the Igbo-speaking region of Nigeria. We confirmed nine new sites where primates are protected as sacred: four with tantalus monkeys (Ch'lorocebus tantalus) and five with mona monkeys (Cercopithecus mona). During 2004-2006, we visited two communities (Akpugoeze and Lagwa > previously known to harbor sacred populations of Ce. sclateri to estimate population abundance and trends. We directly counted all groups and compared our estimates with previous counts when available. We also estimated the size of sacred groves and compared these with grove sizes reported in the literature. The mean size of the sacred groves in Akpugoeze (2.06 ha, n = 10) was similar to others in Africa south of the Sahel, but larger than the average grove in Lagwa (0.49 ha, n = 15). We estimated a total population of 124 Sclater’s monkeys in 15 groups in Lagwa and 193 monkeys in 20 groups in Akpugoeze. The Akpugoeze population was relatively stable over two decades, although the proportion of infants declined, and the number of groups increased. As Sclater’s monkey does not occur in any official protected areas, sacred populations are important to the species’ long-term conservation. Despite the monkeys’ destruction of human crops, most local people still adhere to the custom of not killing monkeys. These sites represent ideal locations in which to study the ecology of Sclater’s monkey and human-wildlife interactions.